Automatic License Plate Recognition Software for Malaysian Vehicle License Plates - Zakaria, Abdul Aziz (Universiti Teknologi PETRONAS, 2016)
Automatic License Plate Recognition (ALPR) is one of the technology which is available worldwide for years. Most ALPR software available nowadays cannot work really well with the Malaysian vehicle license plates due to the unstandardized license plates. Recognizing the Malaysian vehicle license plate which the alphanumerical are being placed really closed next to each other and this will cause problem to the commonly used method in ALPR software called rectangular bounding box or the optical character recognition (OCR) process. Besides, the OCR process is one of the most important method to recognize the characters and numbers on vehicle’s license plate. Hence, a new algorithm should be constructed to be used to overcome these problems. It was proposed by the author that an algorithm that can be used to overcome the rectangular bounding box or the OCR process to test localization and identify Malaysian vehicle license plates with such problems by using Matlab and also still (offline) images.